Guaranteed pure: the Moody Bible Institute, business, and the making of modern evangelicalism - Gloege, Timothy E. W. (University of North Carolina Press, 2015)
Christian workers -- Christian work -- The problem of the masses -- Power for service -- The crisis of evangelical realism -- Christian consumers -- Religion on a business basis -- A consuming faith -- Pure religion -- The name you can trust